Traditional Chinese Medicine in Treating Influenza: From Basic Science to Clinical Applications - Xiong, Yibai; Li, Na Xiao; Duan, Naifang; Liu, Bin; Zhu, Hui; Zhang, Chi; Li, Li; Lu, Cheng; Huang, Luqi (Frontiers in Pharmacology, 2020)
Influenza infection is a highly contagious, acute febrile respiratory disease caused by the influenza virus. Traditional Chinese Medicine(TCM) has dominated plenty of theoretical and practical approaches in the treatment of influenza. It is, therefore, important to highlight the effects of TCM in the clinical treatment of influenza and their impact on inhibiting the growth of this virus in laboratory experiments. We scrutinized existing evidence on whether TCM is effective in clinical applications. Moreover, we described the potential mechanisms of TCM against the influenza virus. Our findings provide analytical evidence that supports the effectiveness of TCM in treating influenza infections as well as their mechanisms against this virus.